The UNC-116(KIF5C) Kinesin-1 Heavy Chain and the UNC-16(JIP3) Cargo Adaptor Regulate Axon Targeting in C. Elegans - (:unkn) unknown (My University, 2023)
Previous data demonstrate variants in hundreds of genes are causative for the formation of neurodevelopmental disorders (NDDs). However, the molecular mechanisms associated with these genes remain poorly understood. Here, we focus on two orthologs of NDD-associated genes, unc-116(KIF5C) and unc-16(MAPK8IP3), and aim to uncover the molecular mechanisms by which they regulate axon targeting. In chapter two, we show that equivalent amino acid changes in the C. elegans ortholog, UNC-116, disrupt proper axon targeting in the PLM mechanosensory neuron. Our work further establishes that kinesin-1 heavy chain UNC-116 and cargo adaptor UNC-16 influence the localization of the Never-in-Mitosis A-Related Kinase 3 (NEKL-3) in the axon. More so, nekl-3 genetically interacts with Regulator of Presynaptic Morphology-1 (rpm-1) to regulate axon termination. In chapter three, we show the equivalent L393P amino acid change in C. elegans ortholog UNC-16 perturbs axon termination but does not affect synaptic vesicle clustering, indicating a specific role for this variant. Additionally, we demonstrate that cargo adaptor UNC-16 promotes axon termination by regulating the endolysosomal system. Furthermore, we provide evidence that UNC-16 regulates both axon termination and synaptic vesicle clustering with the dynein/dynactin complex and leucine-rich repeat kinase 1 (LRK-1). Together, our findings uncover novel mechanisms by which NDD-related genetic variants of KIF5C and MAPK8IP3 regulate axon targeting.
Keywords: Axon Targeting; Axonal Trafficking; Genetics; Molecular Biology; Neurodevelopment; Neurodevelopmental Disorders